The Effectiveness of Contextual Research-Based Teaching Materials on Students’ Learning Independence and Concept Mastery - Linda Lidiawati; Leny Heliawati; Indarini Dwi Pursitasari (Jurnal Pendidikan Indonesia, 2021)
Innovation in teaching materials used in online learning is very urgent based on students’ needs. This study aims to measure the effectiveness of contextual research-based teaching materials to improve students’ learning independence and concept mastery of acid-base solution properties. The research method is Research and Development, referring to Borg and Gall. The research subjects were 60 students and 7 science teachers who have used teaching materials based on contextual research findings. The data collection technique in this study is a test that aims to determine the concept mastery and a questionnaire to measure students’ learning independence. Based on the results of the study, it is known that the average percentage of student learning independence is 78% (Good category). Besides, an average value of 73.83 is obtained with an N-Gain of 64% (Medium category). The use of contextual research-based teaching materials can increase learning independence in terms of information search and concept mastery of acid-base solution properties.